MEKANISME PENYELESAIAN PERKARA ANAK YANG BERHADAPAN DENGAN HUKUM PADA MASYARAKAT DAYAK KANAYATN (Kajian Perbandingan Terhadap Sistem Peradilan Pidana Anak) - Sri Ismawati (Faculty of Law, Universitas Jenderal Soedirman, 2013)
Law enforcement in a delinquency case still colored by formal. The approach of this way can be a crimino-gen factor. Different with Law enforcement of common law of Dayak Kanayant, the settlement of child case is done in discussion and family oriented in one forum of local wisdom of Barukupm Adat. The mecha-nism of Barukupm Adat can be used as a model of child case settlement which is more suitable in need be-cause it is carryng values and protection and balance principles. Key words : ….. resolution mechanism customary law, children in conflict with the law